2018
DOI: 10.1037/ccp0000308
|View full text |Cite
|
Sign up to set email alerts
|

Can working memory training work for ADHD? Development of central executive training and comparison with behavioral parent training.

Abstract: Objective Working memory deficits have been linked experimentally and developmentally with ADHD-related symptoms/impairments. Unfortunately, substantial evidence indicates that extant working memory training programs fail to improve these symptoms/impairments. We hypothesized that this discrepancy may reflect insufficient targeting, such that extant protocols do not adequately engage the specific working memory components linked with the disorder’s behavioral/functional impairments. Method The current study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(75 citation statements)
references
References 67 publications
(166 reference statements)
3
70
2
Order By: Relevance
“…In all BPT sessions, clinicians covered the intervention content by conducting sessions with the treatment manual open as the session guide. Parent-reported treatment feasibility and acceptability were excellent (see Kofler et al in press). As reported below, parent-reported ADHD symptom reductions in this group were consistent with recent reviews of BPT for ADHD (Evans et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In all BPT sessions, clinicians covered the intervention content by conducting sessions with the treatment manual open as the session guide. Parent-reported treatment feasibility and acceptability were excellent (see Kofler et al in press). As reported below, parent-reported ADHD symptom reductions in this group were consistent with recent reviews of BPT for ADHD (Evans et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies propose that working memory deficits occur in approximately 80–85% of children with ADHD when evaluated with cognitive tasks (Coghill et al, 2014 ; Karalunas et al, 2017 ; Kofler et al, 2018a , 2020 ). Studies have also shown that children with ADHD have more working memory deficits than typically developing children (Kasper et al, 2012 ).…”
Section: Cognitive Deficits In Adhdmentioning
confidence: 99%
“…Longitudinal studies show that less severe working memory deficits are associated with lower symptom severity (Halperin et al, 2008 ; van Lieshout et al, 2016 ; Salari et al, 2017 ), and reductions in ADHD symptoms with age seem to be limited to a subset of children who show improvements in working memory over time (Karalunas et al, 2017 ). These studies highlight the significant influence that working memory has on the symptomatology of many children with ADHD and have motivated a recent surge in studies aiming to enhance working memory in children with ADHD (Kofler et al, 2018a ).…”
Section: Cognitive Deficits In Adhdmentioning
confidence: 99%
“…Impaired response inhibition may also affect these children's and adolescents' social problem solving such as generating solutions and making decisions. An efficacy study can test the hypothesis whether enhancing response inhibition through training programs (see further Kofler et al, 2018Kofler et al, , 2020 affects social problem solving in everyday life and ultimately results in a reduction of conduct problems, especially in those children and adolescents with either comorbid ADHD or associated ADHD symptoms. Likewise, an efficacy study can test the hypothesis whether enhancing response inhibition by psychostimulants in children and adolescents with conduct problems and ADHD comorbidity affects social problem solving in everyday life and ultimately results in a reduction of conduct problems.…”
Section: Response Inhibitionmentioning
confidence: 99%
“…In line with a conceptual framework for combined neurocognitive and skill-based treatment approaches for youth with ADHD (Chacko et al, 2014 ), we suggest that executive function training programs are included in the treatment of children and adolescents with conduct problems and poor response inhibition associated with ADHD. While training programs targeting working memory and response inhibition have been less successful than initially anticipated, results of recent studies on central executive training targeting working memory, with effects on response inhibition and hyperactivity, are promising (Kofler et al, 2018 , 2020 ). In a review of interventions and approaches for improving executive functions, Diamond and Ling ( 2016 ) suggest that while challenging of executive functions is necessary for improving them, benefits of improving executive functions will be greater if children’s and adolescents’ emotional, social, and physical needs are also addressed.…”
Section: Response Inhibitionmentioning
confidence: 99%